Factors Affecting Probitability - Sri Dewi Anggadini; Dita Juliana (STIE STEMBI Bandung Business School, 2017)
This study empirically tested the influence of liquidity, operational costs, toprofitabilitas in mining sector companies listed in Indonesia Stock Exchange 2011-2015. The problem with mining companies is the decline in Problemsthat occur in mining companies is the decline in profitability despite liquiditydecreased, operating costs decreased.The research method that is used isdescriptive analysis method verifikatif with unit of analysis researched isfinancial report of mining sector companies listed in BEI in year 2010-2015.And the population of 23 Purposive Sampling and obtained sample researchas many as 30 financial reports from 6 companies. This research that liquidityhas a significant affecting on profitability with a negative relationship,operational costs have a significant effect on profitability with a positiverelationship with a positive relationship.Partially proϔitability dominantinfluenced by operational cost compared with liquidity. Kata Kunci : Operational Cost, Liquidity, and Profitability